Characterizing Hand Infections in an Underserved Population: The Role of Diabetic Status in Antibiotic Choice and Infection Location - Hayden, Andrew J.; Shah, Neil V.; Stroud, Sarah G.; Penny, Gregory S.; Burekhovich, Steven A.; Shah, Aadit T.; Kuehn, Erika; Yang, Andrew; Diebo, Bassel G.; Koehler, Steven M. (Journal of Hand and Microsurgery, 2019)
Introduction Patients with diabetes mellitus (DM) in underserved communities are at greater risk for hand infections. We aimed to describe the features of hand infections presenting to an urban hospital via laboratories, microbiology, and antibiotic choice with respect to diabetic status.Materials and Methods Patients presenting with any hand infection were reviewed and stratified by DM status and infection location. Labs, culture results, antibiotic regimens, and significant predictors of laboratories or infection location were analyzed.Results Fifty-three patients were included: DM (n = 24), no-DM (n = 24), and unknown status (n = 5). Culture rates were comparable between all groups. Mean erythrocyte sedimentation rate (ESR) was significantly higher in DM (76.19 vs. 51.33); mean white blood cell count (WBC) and C-reactive protein (CRP) were comparable. Diabetics had higher odds of increased ESR (odds ratio [OR] = 1.03). Diabetics received vancomycin/piperacillin/tazobactam (VAN/PTZ) significantly more often (52% vs. 8%). Providers treated DM with VAN/PTZ or any VAN-containing regimen more often than with any other regimen. Proximal infections had significantly higher mean CRP (136.9 vs. 50.5) and WBC (5.19 vs. 3.9) and higher CRP (OR = 1.02).Conclusion This study highlights the need for systematic criteria to better risk- stratify patients for appropriate antibiotic treatment. It may not be appropriate to treat both groups differently, as overly aggressive antibiotic selection may contribute to drug-resistance development.
Keywords: hand infections; diabetes; antibiotic selection; methicillin-resistant Staphylococcus aureus; underserved population